Peran Guru Untuk Meningkatkan Etika dan Integritas Siswa dalam Menghadapi Teknologi Digital di SDN Ngoro 2 Jombang - NURJANNAH, SELLA SEFTIA; Claudya Zahrani Susilo (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study is to investigate how educators can help students deal with the impact of technology in the digital age by enhancing their ethics and integrity. Principals and instructors are interviewed as part of a case study approach to qualitative research. According to the study's findings, instructors are crucial in fostering a positive learning environment and establishing moral and ethical principles in their students by maintaining order and student discipline. However, there are barriers such students' access to unrestricted digital use and a lack of parental support. It is anticipated that this study will deepen our understanding of the significance of instructors' roles in forming students' moral character in the digital age, as well as provide recommendations for effective strategies to improve students' ethics and integrity.